2019
DOI: 10.3390/vaccines7040199
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Infection and Immunity in a Suboptimal Vaccination Coverage Setting

Abstract: Despite efforts to improve surveillance and vaccination coverage, measles virus (MeV) continues to cause outbreaks also in high-income countries. As the reference laboratory of the Veneto Region, Italy, we analyzed changes in population immunity, described measles outbreaks, investigated MeV genetic diversity, and evaluated cross-protection of measles vaccination against MeV epidemic strains. Like most European areas, the Veneto Region has suboptimal measles vaccination coverage and is facing a growing public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
0
11
2
Order By: Relevance
“…The pattern of detection rates was similar to that in a previous study reported by Seto et al 15 The results indicate that PBMCs and throat swabs were suitable samples for the detection of patients with SVF. Although the detection rate in urine samples was low in both Seto et al's study (33.3%) 15 and in our data, Sundell et al 14 and Pacenti et al 23 reported a higher detection rate in urine specimens (86.7% and 81.8%, respectively) among patients with breakthrough infections (i.e., those previously immunized or infected with measles). These discrepancies probably depended on the timing of sample collection.…”
Section: Discussioncontrasting
confidence: 63%
“…The pattern of detection rates was similar to that in a previous study reported by Seto et al 15 The results indicate that PBMCs and throat swabs were suitable samples for the detection of patients with SVF. Although the detection rate in urine samples was low in both Seto et al's study (33.3%) 15 and in our data, Sundell et al 14 and Pacenti et al 23 reported a higher detection rate in urine specimens (86.7% and 81.8%, respectively) among patients with breakthrough infections (i.e., those previously immunized or infected with measles). These discrepancies probably depended on the timing of sample collection.…”
Section: Discussioncontrasting
confidence: 63%
“…We used data describing the 2017-2018 measles outbreak in the Veneto Region, located in the North-East of Italy (29). We used 30 sequences (out of 322 suspected cases) analyzed in Pacenti et al (29). Sequences were aligned using the Nextstrain measles workflow (51)(52)(53).…”
Section: -2018 Measles Outbreak In the Veneto Region (Italy)mentioning
confidence: 99%
“…The 50% end point titer of the serum neutralizing titer was calculated using the Reed and Muench method [25]. Serum samples with neutralizing titers of less than eight were considered negative [26]. A positive and negative control serum (Liaison Measles IgG Ctr) were included in each assay.…”
Section: Measles Microneutralization Testmentioning
confidence: 99%